IMPLEMENTATION OF CORPORATE GOVERNANCE AT POSCO - Bahri Sriwijaya, Sayid (Dinasti International Journal of Management Science, 2020)
Corporate Governance is a structure consisting of shareholders, directors, managers, a set of objectives to be achieved by the company, and tools that will be used in achieving goals and monitoring performance. This study aims to determine the application and benefits of Corporate Governance at POSCO, using descriptive qualitative analysis methods. The application of the principles of Corporate Governance at POSCO has been carried out since 1997 through the management philosophy of "Corporate Citizenship: Building a Better Future Together". For example, the principle of equality is carried out by POSCO by making stronger shareholder protection through the Cumulative Voting System to strengthen the rights of small shareholders. The principle of independence is implemented through the separation of share ownership from company management, assigning 7 out of 12 members of the BoD (Board of Directors) to be external directors, and to separate the functions of the CEO and Chairman of the Board. The principle of responsibility is applied through the establishment of an audit committee, the Corporate Social Responsibility program. Corporate Governance had earned POSCO many national and international awards